Allogeneic Vγ9Vδ2 T-Cell Therapy Promotes Pulmonary Lesion Repair: An Open-Label, Single-Arm Pilot Study in Patients With Multidrug-Resistant Tuberculosis - Liang, Juan; Fu, Liang; Li, Man; Chen, Yuyuan; Wang, Yi; Lin, Yi; Zhang, Hailin; Xu, Yan; Qin, Linxiu; Liu, Juncai; Wang, Weiyu; Hao, Jianlei; et al. (Frontiers in Immunology, 2021)
The WHO’s “Global tuberculosis report 2020” lists tuberculosis (TB) as one of the leading causes of death globally. Existing anti-TB therapy strategies are far from adequate to meet the End TB Strategy goals set for 2035. Therefore, novel anti-TB therapy protocols are urgently needed. Here, we proposed an allogeneic Vγ9Vδ2 T-cell-based immunotherapy strategy and clinically evaluated its safety and efficacy in patients with multidrug-resistant TB (MDR-TB). Eight patients with MDR-TB were recruited in this open-label, single-arm pilot clinical study. Seven of these patients received allogeneic Vγ9Vδ2 T-cell therapy adjunct with anti-TB drugs in all therapy courses. Cells (1 × 108) were infused per treatment every 2 weeks, with 12 courses of cell therapy conducted for each patient, who were then followed up for 6 months to evaluate the safety and efficacy of cell therapy. The eighth patient initially received four courses of cell infusions, followed by eight courses of cell therapy plus anti-MDR-TB drugs. Clinical examinations, including clinical response, routine blood tests and biochemical indicators, chest CT imaging, immune cell surface markers, body weight, and sputum Mycobacterium tuberculosis testing, were conducted. Our study revealed that allogeneic Vγ9Vδ2 T cells are clinically safe for TB therapy. These cells exhibited clinical efficacy in multiple aspects, including promoting the repair of pulmonary lesions, partially improving host immunity, and alleviating M. tuberculosis load in vivo, regardless of their application in the presence or absence of anti-TB drugs. This pilot study opens a new avenue for anti-TB treatment and exhibits allogeneic Vγ9Vδ2 T cells as promising candidates for developing a novel cell drug for TB immunotherapy. Clinical Trial Registration (https://clinicaltrials.gov/ct2/results?cond=&term=NCT03575299&cntry=&state=&city=&dist=) ( NCT03575299).